Charge transfer complexes: a review survey - Vahideh Hadigheh Rezvan (Results in Chemistry)
Charge transfer complexes (CTCs) are formed when an electron donor interacts with an electron acceptor. A new compound (CTC) is generated through the formation of hydrogen bonds or charge transfer interactions. This review examines the synthesis, characteristics, and documented examples of CTCs. It highlights recent advancements in the utilization of CTCs across various sectors and explores their potential for future applications, as well as the challenges that must be addressed to develop new CTCs and investigate their uses. These complexes exhibit unique properties that distinguish them from traditional ionic, covalent, and coordination bonds. Some CTCs, especially those involving drugs, possess biological properties such as antibacterial and antiviral effects; experimental and molecular docking studies have been conducted. The introductory section of the review summarizes CTCs, emphasizing the relationship between donors and acceptors in the synthesis of new molecular structures. Furthermore, this paper explores the application of density functional theory in analyzing intermolecular CTCs, focusing on the estimation of structures, binding energies, and CT transitions. The review discusses various types of CTCs, such as protonic CTCs or hydrogen-bonded charge-transfer (HB-CT) complexes, and the thermodynamics involved in the process governing the interaction between the donor and acceptor. Additionally, the paper highlights the wide-ranging applications of CTCs in numerous fields, including biological sciences, thermo-electrics, photoconductors, light detectors, photocatalysts, materials science, medicine, optoelectronic devices, nonlinear optical (NLO) materials, chemo-sensors, electrical conductors, surface chemistry, molecular nanodevices, and photographic technology, among others. It summarizes various synthetic methods for CTC fabrication, including co-crystallization, thin film deposition, electrochemical synthesis, solvothermal and hydrothermal techniques, stoichiometric reactions, and molecular assembly approaches. Each method offers unique advantages in controlling the structural, electronic, and morphological properties of CTCs, thereby influencing their stability and functionality. These techniques enable the tailored design of CTCs for their applications in various fields such as photovoltaics, sensors, and optoelectronic devices. Understanding and optimizing these fabrication strategies is essential for advancing the development of efficient CT materials. This paper also reviews diverse analytical techniques employed in studying CTCs, highlighting their roles in elucidating the formation, structure, and properties of these systems. Spectroscopic methods such as UV–Vis and fluorescence spectroscopy are crucial for confirming CTC formation, analyzing electronic transitions, and investigating CT kinetics and dynamics. Time-resolved fluorescence further provides insights into electron transfer rates and excited-state behaviors. Complementary techniques like NMR, IR (FTIR), X-ray crystallography, and thermal analysis (TGA, DSC, DMA) offer detailed structural, vibrational, and thermal stability information. Electrochemical methods, including cyclic voltammetry and potentiometry, enable characterization of redox properties and CT stability. Advanced computational approaches, such as DFT and molecular dynamics simulations, support understanding of electronic structures and interactions. Additional techniques like electron paramagnetic resonance (EPR), photo-titration, and the Benesi-Hildebrand equation provide quantitative insights into complex formation, binding constants, and photophysical behaviors. Together, these methods provide a comprehensive understanding of CTC behavior, supporting their development for applications in organic electronics, sensors, and photonics.